Vamos tirar a educação do quadro negro em que ela está: a nucleação escolar como proposta da reorganização e modernização na educação rural de Uberlândia/MG (1980 a 1990) - Silveira, Tânia Cristina da (2019)
The research has the history of rural schooling in the city of Uberlândia / MG as its theme, with emphasis on the process of rural schools nucleation that was begun in 1984. The time cut began in 1980 and has its end in 1990. This beginning arises from the need to ascertain the background that justified the nucleation, and the end is established due to the process closure. The theoretical foundation is based on the assumptions of Cultural History and of the Humanistic Geography. Whereas the general objective of the study is to understand how the nucleation of the rural schools of Uberlândia was conceived in the scope of Participatory Democracy; understand the public power situation (and if there was) and how was the participation of the rural community in the accomplishment of this measure in rural educational establishments. The examined thesis refers to the issue that, despite official discourses announcing the purpose of school nucleation as a possibility to “modernize” rural institutions, from the physical structure to the administrative and pedagogical aspects, inspired by the urban model of primary schooling, the rural schools after the nucleation were not able to be compared to the urban schools. Moreover, according to this same discourse, this process implied the rural community participation, however, its occurrence had not been effective, since it was in charge of the municipal public power the consensus regarding its validation. In order to achieve the desired goal, we use the methodology of documentary and bibliographic research using the following documents: federal, state and municipal legislation; teaching programs; municipal budgets; books of minutes of the Legislative Power of the period 1980-1990; censuses and educational statistics; periodical press, especially newspapers; iconography (photographs and maps) and oral history through eight interviews with former mayor, former pedagogical coordinator, former pedagogical advisor, former teachers, former student and former student's mother. In mayor Zaire Rezende’s administration (1983-1988), the rural community participation in the nucleation process occurred in the measure proposed by mentioned administration, however, it has prompted a “shy experience” of democratic organization among the farming population. The period was mainly based on the physical infrastructure development that was necessary for that change in rural municipal establishments, as well as in school transport organization, essencial conditions to realize this project. The Virgílio Galassi's administration (1989-1992) proceed with and terminated the process, showing greater demand regarding the organization of the administrative and pedagogical aspects of the core schools. The rural communities has instituted as a representation the proposal of the school transport; but the nucleus, serial and multiple teacher's schools were not remembered, unlike the isolated school, represented as a place of inhabitants socialization of the the farming communities. In the rural space, a place of school, isolated institutions were designated in the mental image of communities with attributes of legibility, identity, structure and meaning, as well as the presence of resistance in the implementation of the integration of a rural municipal school, Tenda.